2020
DOI: 10.1017/s1751731119001605
|View full text |Cite
|
Sign up to set email alerts
|

Review: Endocrine pathways to regulate calcium homeostasis around parturition and the prevention of hypocalcemia in periparturient dairy cows

Abstract: Calcium homeostasis is crucial for the normal function of the organism. Parathyroid hormone, calcitriol and calcitonin play critical roles in the homeostatic regulation of calcium. Serotonin and prolactin have also been shown to be involved in the regulation of calcium homeostasis. In modern dairy cows, the endocrine pathways controlling calcium homeostasis during non-lactating and non-pregnant physiological states are unable to fully support the increased demand of calcium required for milk synthesis at the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…In lactating animals, PTH-related peptide (PTHrP) is secreted by the mammary gland into both milk and blood. Although it can bind the PTH receptor, it is probably not Table 1 Results from balance studies done with different ruminant species: intake, urinary excretion (UEX), pre-intestinal (PRE) and intestinal (INT) net absorption (ABS), faecal excretion (FEX) in grams per day, apparent digestibility (AD) in percentage Müschen et al (1988) involved in vitamin D metabolism but likely to act on bone mobilisation (Hernández-Castellano et al, 2019). In addition, it was suggested to exert effects on renal Ca handling such as prolactin (Herm et al, 2015).…”
Section: Endocrine Control Of Calcium and Phosphate Transportmentioning
confidence: 99%
“…In lactating animals, PTH-related peptide (PTHrP) is secreted by the mammary gland into both milk and blood. Although it can bind the PTH receptor, it is probably not Table 1 Results from balance studies done with different ruminant species: intake, urinary excretion (UEX), pre-intestinal (PRE) and intestinal (INT) net absorption (ABS), faecal excretion (FEX) in grams per day, apparent digestibility (AD) in percentage Müschen et al (1988) involved in vitamin D metabolism but likely to act on bone mobilisation (Hernández-Castellano et al, 2019). In addition, it was suggested to exert effects on renal Ca handling such as prolactin (Herm et al, 2015).…”
Section: Endocrine Control Of Calcium and Phosphate Transportmentioning
confidence: 99%
“…Since consistent and appropriate milking is difficult and blood calcium concentration can be relatively easily corrected through exogenous administration, some farms use a modified strategy where calcium injection is first administered to prevent milk fever, and mastitis is prevented by regulating or not regulating the milking levels (Deb et al, 2013;Hernández-Castellano et al, 2020). In this study, the modified strategies were divided into PCI with gradually milking group (CG) and PCI with complete milking group (CC).…”
Section: Resultsmentioning
confidence: 99%
“…This result is the first of its kind to demonstrate that PCI during the colostrum period increases milk fever recurrence. Based on a previous study that reported successful prevention of milk fever by optimizing the calcium metabolism in dairy cattle by limiting calcium intake in late dry period, recovery of milk fever in CG and CC by temporal exogenous calcium treatment leads to failure in proper stimulation of postpartum hypocalcemia and obtain physiology optimal for milk production resulting in higher recurrence of milk fever (Sørensen et al, 2002;Jeon and Rho, 2019;Hernández-Castellano et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Improving the mobilization of calcium from bone and the absorption of calcium from the diet are two major processes that prevent the decrease in blood calcium in dairy cows. The mobilization of calcium from bone can be accomplished by feeding a calcium-deficient diet or negative dietary cation-anion difference in the pre-calving period [57]. In addition, the infusion of 5-hydroxytryptophan can also improve blood calcium concentrations around parturition [58].…”
Section: Application As a Source Of Calcium To Prevent Milk Fever In mentioning
confidence: 99%
“…The high concentrations of ionized calcium in the rumen lumen induce a chemical gradient that passively transports ionized calcium from the mucosa through the tight junctions towards the extracellular space on the serosa side, increasing the concentrations of ionized calcium in the blood [64]. The administration of a ruminal calcium bolus (approximately 43 g of calcium) has been used to restore blood calcium concentrations [57] by improving the amount of calcium that can be absorbed from feed.…”
Section: Application As a Source Of Calcium To Prevent Milk Fever In mentioning
confidence: 99%